2021
DOI: 10.1002/tox.23119
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorotridecanoic acid inhibits fetal Leydig cell differentiation after in utero exposure in rats via increasing oxidative stress and autophagy

Abstract: Perfluorotridecanoic acid (PFTrDA) is a long-chain perfluoroalkyl substance, and its effect on the differentiation of fetal Leydig cells remains unclear. The objective of this study is to explore the effect of in utero PFTrDA exposure on the differentiation of fetal Leydig cells and investigate its underlying mechanisms. Pregnant Sprague-Dawley female rats were daily administered by gavage of PFTrDA at doses of 0, 1, 5, and 10 mg/kg from gestational day 14 to 21. PFTrDA had no effect on the body weight of dams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
(137 reference statements)
0
5
0
Order By: Relevance
“… 68 PFTrDA also down‐regulated fetal Leydig cell (FLC) genes such as Insl3 , Lhcgr , Scarb1 , Nr5a1 , Cyp17a1 , Star , Hsd3b1 , and Dhh , antioxidants ( GPX1 , SOD1 , CAT ) and induced autophagy suggesting that PFTrDA inhibits the differentiation of fetal Leydig cells in male pups. 68 In addition, exposure to perfluorooctanoic acid (PFOA; 25 mg/kg) in female mice decreased the weight and length of the fetus, diameter, and weight of the placenta, dead fetuses, and dead macerated fetuses in PFOA‐treated animals because of mitochondria dysfunction. 69 Due to unique physicochemical properties and industrial applications graphene oxide (GO) is used as a filter material for removing perfluorinated substances and trihalomethanes from drinking water.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“… 68 PFTrDA also down‐regulated fetal Leydig cell (FLC) genes such as Insl3 , Lhcgr , Scarb1 , Nr5a1 , Cyp17a1 , Star , Hsd3b1 , and Dhh , antioxidants ( GPX1 , SOD1 , CAT ) and induced autophagy suggesting that PFTrDA inhibits the differentiation of fetal Leydig cells in male pups. 68 In addition, exposure to perfluorooctanoic acid (PFOA; 25 mg/kg) in female mice decreased the weight and length of the fetus, diameter, and weight of the placenta, dead fetuses, and dead macerated fetuses in PFOA‐treated animals because of mitochondria dysfunction. 69 Due to unique physicochemical properties and industrial applications graphene oxide (GO) is used as a filter material for removing perfluorinated substances and trihalomethanes from drinking water.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, exposure to PFOA affects porcine oocyte maturation, and exposure to PFOA enhanced reactive oxygen species production, protein carbonylation, and DNA damage in cumulus cells 67 . Administration of perfluorotridecanoic acid (PFTrDA) to pregnant Sprague–Dawley female rats showed decreased serum testosterone levels at 1 mg/kg and also promoted abnormal aggregation of fetal Leydig cells at doses of 5 and 10 mg/kg 68 . PFTrDA also down‐regulated fetal Leydig cell (FLC) genes such as Insl3 , Lhcgr , Scarb1 , Nr5a1 , Cyp17a1 , Star , Hsd3b1 , and Dhh , antioxidants ( GPX1 , SOD1 , CAT ) and induced autophagy suggesting that PFTrDA inhibits the differentiation of fetal Leydig cells in male pups 68 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, in the present study, we identified some differentially methylated genes whose deregulation by oxidative stress has already been reported. Among the genes identified we highlight LHCGR , TGFB1 , SEPT9 and BNC2 in the HbSS group [ 43 46 ], and CERS6 , GATA4 , HLA -G and PAX3 in the HbSC group [ 47 50 ]. These findings suggest that oxidative stress may be modulating these genes through methylation in the studied patients.…”
Section: Discussionmentioning
confidence: 99%